WORD FORMATION PROCESSES IN THE NAMES OF DIGITAL HEALTH PLATFORMS - Juwita, Imas Nita; Aulia, Hernita Ratna (Prologue: Journal on Language and Literature, 2025)
This research is conducted to examine the word formation processes contained in the naming of digital health platforms in Indonesia  This research would mainly focus on analyzing how the patterns of language, culture and region influence the trends of name creation in the global digital health sector. This research uses qualitative research in a morphosemantic approach. From the result analysis, some types of word-formation processes include compounding, blending, and clipping,to identify the strategies behind these naming conventions.The findings reveal that digital health platforms in Indonesia often combine local Indonesian elements, such as "Sehat"  and "Dokter", with global English terms like "Health"and"Go”. The blending of local and global components illustrates the contradictory impact of globalization and the necessity to maintain cultural relevance. The study emphasizes that cultural qualities,like as friendliness and approachability, are integrated into company names through welcomes like "Halo", while the incorporation of English phrases seeks to convey a contemporary and professional image. This research illustrates that the interaction between language processes and cultural context is crucial for developing significant and memorable brand identities. These findings enhance linguistic research and offer practical insights for branding strategies in the digital health sector, especially in culturally varied markets such as Indonesia.